Transforming Patient Complaints: Strategic Layout and Operational Processes Enhancements at Pharmacy Unit - Nugraha, Aditya; Untari, Rustina (Journal of Management and Business Environment (JMBE), 2025)
Hospital, as a healthcare provider, consists of various interrelated service units. Pharmaceutical services for outpatient, inpatient, and operating room are provided by the pharmacy units and they need good operational management to maintain the speed of service. However, with the increasing number of patients, there has been a drastic decline in pharmacy service speed, leading to a rise in patient complaints and a decrease in patient satisfaction index, which, if unaddressed, may result in patient loss. This study measured the impact of changes in room layout, workflow improvements, pharmacy unit manpower productivity, and alteration of drug packaging on complaint numbers and satisfaction index of the patients at Primaya Hospital Semarang. A Likert scale questionnaire was to assess patient satisfaction and record complaints received via WhatsApp, Google Reviews, email, Instagram, or directly to the customer service unit. The measurements were taken before the intervention and after implementation of the changes. The implementation of these four operational interventions decreased significantly the complaint numbers over time accompanied by an increase in patient satisfaction index.